Nurses’ knowledge, attitude and practices (KAP) during flood disaster affected east coast region in Malaysia - Aung, Khin Thandar; Nurumal, Mohd. Said; Ahayalimudin, Nurul'Ain (International Organization of Scientific Research (IOSR), 2019)
The incidence rate of disaster and the severity of the resulted damages are increasing around the world. A disaster is a severe destruction of communities leading to great losses of human life. As the victims in disaster area might be required critical and intensive care, the roles of nurse are vital in disaster management. Most of studies that related to KAP of nurses regarding disaster management are present, however, little is known about the KAP of nurses during flood disaster. This study aimed to explore the nurses' KAP during flood disaster affected East Coast Region of Malaysia. A quantitative cross- sectional study was done on 197 registered nurses (RNs) who involved in flood disaster response in 2014 at three tertiary hospitals that affected flood in 2014. Purposive sampling was used to choose information-rich participants who were knowledgeable about or had a similar experience and willing to be involved in the study. The questionnaire developed by Nurul’Ain Ahayalimudin (2012) on ‘KAP of nurses in disaster management’ was used as a research instrument and analyzed with SPSS version 22. As the result, the majority of the participants had an adequate knowledge and practice, and portrayed a positive attitude towards disaster management during the flood disaster. As a conclusion, most of the nurses had good knowledge and attitude and also good practice during flood disaster management. Disaster management training should be more emphasized for hospital nurses and help them to improve their awareness and readiness for disaster response outside of the hospital environment.